ANALISIS KIMIA JENIS KAYU KECING BUNGA (Lithocarpus elegans) DAN KAYU NIPIS KULIT (Memecylon garcinioides) BERDASARKAN KETINGGIAN BATANG - Gurning, Boy; Wardenaar, Evi; Husni, Harnani (JURNAL HUTAN LESTARI, 2017)
The chemical properties of wood flowering (Lithocarpus elegans) and lime leather (Memecylon garcinioides) based on wood species, the chemical properties of wood for the extractive content of alcohol soluble benzene lime leather is higher than that of the flower wood with a mean rate of 2, 7111%; 2.5343%. While the lignin level of wood flower kecing is higher than the lime leather with the average value of 16.6030%; 16,4189% and leather holocellulose content of leaf wood was higher compared to wood flower with average value of 86,8927%; 83.4929%. Based on the height of the stem for the extractive substance of alcohol-soluble benzene, the highest average was in the center of 2.9812%, and the lowest at the end of 2.3525%. For lignin content the highest average value is at the tip of 17,5200%, and the lowest at the center of 15.8084%. While for the highest holocellulose value is at the base of 87.0459%, and the lowest at the center of 81.8711%.Keywords: Flowering Wood and Lime Leather, Wood Chemistry,